2004
DOI: 10.1002/jsfa.1663
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation of maize and bean flours: effects on starch physicochemical properties

Abstract: In an earlier study (Rombo GO et al, J Sci Food Agric 81: 497-502 (2001)) it was found that the in vitro starch digestibility of raw and cooked maize and bean flours was increased by irradiation of the flours at 2.5 kGy, but there was a reduction in starch digestibility at doses above 2.5 kGy. Experiments were performed to determine what effects irradiation had on the molecular properties of the starch in maize and bean flours. Increasing irradiation dose caused an increased proportion of β(1-3)-and β(1-4)-bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 23 publications
6
34
0
Order By: Relevance
“…Our previous results also showed that gamma irradiation decreased the T p (27C decrease) and DH of rice flour, after being irradiated at 50 kGy [2]. Increases in T o and T p after irradiation were reported in wheat and potato starches [11,15] and bean flour [17]. However, the T p of wheat starch decreased after being irradiated with 446 kGy [11].…”
Section: Thermal Propertiesmentioning
confidence: 61%
See 3 more Smart Citations
“…Our previous results also showed that gamma irradiation decreased the T p (27C decrease) and DH of rice flour, after being irradiated at 50 kGy [2]. Increases in T o and T p after irradiation were reported in wheat and potato starches [11,15] and bean flour [17]. However, the T p of wheat starch decreased after being irradiated with 446 kGy [11].…”
Section: Thermal Propertiesmentioning
confidence: 61%
“…However, the T p of wheat starch decreased after being irradiated with 446 kGy [11]. Rombo et al [17] also reported that the T o decreased in maize flour after gamma irradiation. The DH was reported to decrease in potato and wheat starches [11,15] and bean flour [17], but to increase in maize flours [17] after irradiation.…”
Section: Thermal Propertiesmentioning
confidence: 96%
See 2 more Smart Citations
“…Gamma irradiation had been applied to modification of the properties of konjac glucomannan (Prawitwonga, Takigamia, & Phillips, 2007), starch (Abu, Duodu, & Minnaar, 2006;Bao, Ao, & Jane, 2005;Rombo, Taylor, & Minnaar, 2004), chitosan (Chen, Song, Liu, & Fang, 2007;Choi, Ahn, Lee, Byun, & Park, 2002;Huang, Shen, Sheng, & Fang, 2005) and its blend film (Zhai, Zhao, Yoshii, & Kume, 2004). The effects of irradiation on these polysaccharides had been shown to include depolymerisation and degradation (Sokhey & Hanna, 1993), resulting in decreased viscosity or cross-linking (Nagasawa et al, 2004;Rombo, Taylor, & Minnaar, 2001), increased water solubility and acidity (Bao, Shu, Xia, Bergman, & McClung, 2001), and the gelatinization enthalpy was reported to increase (Rayas-Duarte & Rupnow, 1993;Rombo et al, 2001), or decrease (Bao & Corke, 2002).…”
Section: Introductionmentioning
confidence: 99%